2005
DOI: 10.1016/j.jeurceramsoc.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Internal friction investigation of phase transformation in nearly stoichiometric LaMnO3+δ

Abstract: Rhombohedral LaMnO 3+δ powders, prepared by two different soft chemistry routes (co-precipitation and hydrothermal synthesis), are sintered at 1400 • C for 2 h in air. Measurements of internal friction Q −1 (T) and shear modulus G(T), at low frequencies from −180 to 700 • C under vacuum, evidence three structural transitions of nearly stoichiometric orthorhombic LaMnO 3+δ . The first one, at 250 or 290 • C, depending on the processing followed, is associated to either a Jahn-Teller structural transition or a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…This also indicates a large increase in oxygen vacancies in region I and its invariance in region II [9]. A change in slopes is observed in a temperature region 260-290 • C probably due to the Jahn-Teller structural transition as observed earlier for the nearly stoichiometric LaMnO 3+ı [32]. It is also worth mentioning that the TG increases with increasing x, suggesting an increase in oxygen vacancies.…”
Section: Thermal Propertiessupporting
confidence: 68%
“…This also indicates a large increase in oxygen vacancies in region I and its invariance in region II [9]. A change in slopes is observed in a temperature region 260-290 • C probably due to the Jahn-Teller structural transition as observed earlier for the nearly stoichiometric LaMnO 3+ı [32]. It is also worth mentioning that the TG increases with increasing x, suggesting an increase in oxygen vacancies.…”
Section: Thermal Propertiessupporting
confidence: 68%
“…Internal friction measurements can be used to evaluate phenomena which affect the mechanical performance of a material, such as the ageing after deformation, precipitation, changes of Young modulus or shear modulus, and phase transformations [13,14]. Some internal friction applications which involve phase transformations are the study of martensite in alloys with shape memory effect [17] and phase transformations in magnetic oxides [18]. Studies of mechanical relaxation spectroscopy in copper alloys [19] showed that the higher internal friction in martensite phase was caused by movement of twin boundaries and martensites plate boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…The average diameter was obtained by the slope inverse of the line obtained. The distortion was obtained from the y-intercept [31].…”
Section: Halder and Wagner Methodmentioning
confidence: 99%